Determinanten der Standortattraktivität Deutschlands für die Ernährungswirtschaft Ergebnisse einer Expertenbefragung; Determinants of Germany's Attractiveness as a Location for the Food Industry Results from an Expert Survey - Julia Hoḧler; Svenja Mohr; Anne Piper (German Journal of Agricultural Economics (GJAE), 2020)
– The choice of location is a complex decision-making problem. Particularly in the food industry, other factors, such as the public perception of the sector, are playing an increasingly important role in addition to the known location factors. As part of an expert survey, 70 experts from four areas of the food industry were asked to assess various location factors. The survey results were used in a structural equation model to determine the relevance of the various influencing factors for the perceived attractiveness of the location. The perception of (or in) the public proves to be a particularly important determinant.
Keywords: 330